PENGARUH HYPNOBIRTHING TERHADAP NYERI PERSALINAN PADA IBU BERSALIN INPARTU KALA I DI KPRI CITAMA CITAYAM TAHUN 2024 - Damanik, Susi Berliana; Noviyanti, Ernita Prima; Wulandari, Ratna (Universitas Fort De Kock, 2025)
The World Health Organization (WHO) records that around 830 women worldwide die every day due to complications related to pregnancy or childbirth, and as much as 99%. The phenomenon in some healthcare facilities, many laboring mothers scream and feel confused facing the labor process they are experiencing, and generally, healthcare providers consider this to be a common experience for every laboring mother. The purpose of this report is to determine the effect of Hypnobirthing on labor pain in parturient mothers in the first stage of labor at Citama Clinic. This study uses the Quasi-Experimental method. The population of this study consists of 40 pregnant women, and the sample size taken is above 20 because it is considered to approach a large number, which, if plotted, will approximate a normal curve. The normal curve is an indication of the presence of a natural phenomenon that, in large numbers, will always form a normal curve. The results of this study indicate that there is no significant difference between the experimental class and the control class before and after for patients who were not given hypnobirthing during the first stage of labor at Citama Clinic. The recommendation from this researcher is that pregnant women should seek comprehensive information about childbirth, especially in facing the labor process with the hypnobirthing method